PERUBAHAN NILAI SOLIDARITAS PERKAWINAN DAN KEMATIAN PADA MASYARAKAT DUSUN EMPAONG AKIBAT PERKEBUNAN SAWIT - Kurniawati, E Titin; Aminuyati, Aminuyati; Wiyono, Hadi; Mashudi, Mashudi; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine changes in the value of solidarity of marriage and death in the Empaong Hamlet community due to oil palm plantations. This research uses qualitative research methods. Data collection techniques using observation, interviews with the people of Empaong Hamlet, and documentation. data sources used primary data and secondary data. Data analysis techniques are obtained through data reduction, data presentation and conclusion drawing. The technique of testing the validity of this research data using triangulation. The results of the study showed that the solidarity value of marriage and death in Empaong Hamlet before the existence of oil palm plantations was seen from the community always participating such as working together, cooperating and helping in the form of food donations. After the existence of oil palm plantations, there was a change in the solidarity value of marriage and death in Empaong Hamlet where changes occurred in the community who owned oil palm plantations no longer participated in the form of labor but participated in the form of donations of money and basic necessities to families who held marriage and death events. Factors causing changes in the solidarity values of marriage and death are internal factors including economic and egoistic factors while external factors include modernization factors.